Η ΣΦΑΓΗ ΣΤΟΝ ΙΠΠΟΔΡΟΜΟ ΤΗΣ ΘΕΣΣΑΛΟΝΙΚΗΣ ΤΟ 390 Μ.Χ. ΕΝΑ ΠΟΛΙΤΙΚΟ ΕΚΓΛΗΜΑ ΤΟΥ ΘΕΟΔΟΣΙΟΥ Α’ - ΓΙΑΤΣΗΣ ΣΩΤΗΡΗΣ Γ. (Eoa kai Esperia, 2006)
The aim of this paper is to discuss some unclear aspects concerning thetragic massacre, which took place at the hippodrome of Thessaloniki in 390AD, after Theodosius’ I (379-395 AD) imperial order. It has been written that7.000 or 15.000 people were barbarously murdered in one day. The mainquestion is why Theodosius I ordered such a big massacre, since the reason ofhis crime was a serious act of hooliganism assassination of the magistermilitum of the city Buterichus. Nevertheless, there are indications thatTheodosius I ordered the massacre in order to satisfy the Goths who lived inthe city as mercenaries. The position of St Ambrosius, who denied the entryof Theodosius I in the church at Mediolanum and compelled him to dopenance is also discussed, Theodosius I apologized in front of the people forhis crime. Both original and secondary sources are used, in particular thosenot sufficiently examined. These are the text of Nikephoros KallistosXanthopoulos (14th century) and the monography of Kolias (1935) thatapproached the subject efficiently.